Reading Culture Improvement Management To Improve Literature Quality - Sutopo, Bambang; Wasliman, Iim; Mulyanto, Agus; Rifki Noval, Sayid (International Journal of Educational Research & Social Sciences, 2022)
Most of the knowledge is presented in the form of written language so that it requires someone to do reading activities in order to gain knowledge. Therefore, learning to read has a very strategic position in education and teaching. This reading ability cannot be obtained naturally, but through a learning process which is partly the responsibility of the teacher. Schools that are concerned with a quality culture will certainly manage this reading culture effectively and efficiently to improve the quality of their graduates and ultimately have an impact on school quality. The research approach used is qualitative. The data collection method used is the case study method. Data collection techniques used are observation techniques (observations), interview techniques, documentation studies. Regarding data analysis techniques using nonstatistical analysis techniques. The results showed that the management of improving reading culture to improve student literacy in two SMAITs was carried out by the school, both principals and teachers through various approaches and applying learning management principles. However, it turns out that the results have not been effective, because the achievement of student learning outcomes has not been able to meet the minimum standard of completeness criteria (KKM) that has been set by each school. The learning planning in the two SMAITs is in accordance with the applicable regulations. However, in its preparation it has not determined the target for the completion of the planning, so it is difficult to determine the target for achievement; In the implementation of learning, learning resources in the two SMAITs are still very limited, making it difficult for students to carry out learning. The learning environment in the two SMAITs is very conducive because they do not face many distractions so that students can study seriously and with full concentration, although support from the community is still limited; The learning infrastructure in the two SMAITs is still lacking, especially the Indonesian Language Laboratory space is not adequate so that learning in the laboratory to develop literacy often cannot be carried out perfectly. This turned out to be an obstacle to the achievement of the quality of Indonesian language learning and literacy. The process of implementing Indonesian language learning in the two SMAITs uses more face-to-face meetings with the main activity being the teacher in delivering Indonesian language material. Practical literacy learning is rarely carried out because it does not yet have an adequate Indonesian Language Laboratory, this has an impact on students' abilities in learning Indonesian, prioritizing cognitive aspects rather than affective and psychomotoraspects (literacy).